Practicum-Based Inquiry Learning to Improve the Scientific Attitude of Students at SMA Negeri 1 Suka Makmur Aceh Besar - Suryati, Indah; Akmal, Nurul (Universitas Serambi Mekkah, 2021)
The purpose of this study was to determine the increase in scientific attitudes of students taught by practicum-based inquiry learning. The research started with the preparation of the scientific attitude observation sheet instrument. The analyzed data are qualitative. Qualitative data of this study was data from the observation of students' scientific attitudes using the percentage formula. The method used in this study was a quasi-experimental method: treatment of one variable and no control classwith pretest-posttest design. This research used a descriptive research to describe students' scientific attitudes. The average value of the highest scientific attitude of students was on the open aspect of 70.27%, while the average value of the lowest scientific attitude of students was on the curiosity indicator of 56.33%. Thus, it can be concluded that the students’ scientific attitude increased through the process of practical activities on arthropods and molluscs material using inquiry learning occurred with a fairly good category 63.82%. Keywords: inquiry learning, practicum-based, scientific attitude.